Beyond The Boundaries: Interdisciplinary Collaboration As The Engine Of Innovation And Impact At The Faculty Level - Isabirye, AK.; Moloi, KC (Journal of Ecohumanism, 2025)
This study examined interdisciplinarity as a key driver of innovation and societal impact at the faculty level. Drawing on both historical and contemporary research, it argues that complex societal challenges—such as climate change, public health, urbanisation, and technological disruption—require knowledge creation and teaching practices that extend beyond single-discipline boundaries. The review gathers evidence of interdisciplinary benefits, including increased creativity, better problem framing, greater policy relevance, and improved student skills in critical thinking and collaboration. At the same time, it highlights ongoing challenges: epistemic tensions, misalignment in curriculum and assessment, faculty workload pressures, publication and funding hurdles, and risks of superficial integration. To address these issues, the paper proposes institutional strategies for effective implementation: targeted faculty development, dedicated cross-disciplinary research centres, structurally embedded experiential and project-based learning, mentoring and networking programmes, customised assessment rubrics and recognition systems, and investment in supporting infrastructure and governance. It also stresses the importance of reflexive ethics and fairness audits in technology-intensive projects. The analysis provides practical recommendations for universities to realign incentives, build capacity, and implement inclusive evaluation mechanisms that encourage interdisciplinary outputs. The conclusion states that interdisciplinarity can significantly boost innovation and societal impact, provided it is supported by coherent design, ongoing institutional backing, and rigorous, context-sensitive evaluation.